2020
DOI: 10.3390/w12102920
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Temporal Changes of Precipitation Quality in Slovak Mountain Forests

Abstract: The paper is focused on the evaluation of long-term changes in the chemical composition of precipitation in the mountain forests of Slovakia. Two stations with long-term measurements of precipitation quality were selected, namely the station of the EMEP (European Monitoring and Evaluation Programme) network Chopok (2008 m a.s.l.) and the station of the ICP Forests (International Co-operative Programme on Assessment and Monitoring of Air Pollution Effects on Forests) network Poľana-Hukavský grúň (850 m a.s.l.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Long-term temporal precipitation quality changes in Slovak mountain forests were studied by Mind'aš et al [4]. Authors found significant declining trends for almost all evaluated chemical components (S-SO4, N-NH4, N-NO3, Ca, Mg, and K), which can significantly affect element cycles in mountain forest ecosystems.…”
Section: Overview Of the Special Issue Contributions 21 Hydrological And Atmospheric Aspects Of Natural Hazards In Changing Climate And Ementioning
confidence: 99%
See 1 more Smart Citation
“…Long-term temporal precipitation quality changes in Slovak mountain forests were studied by Mind'aš et al [4]. Authors found significant declining trends for almost all evaluated chemical components (S-SO4, N-NH4, N-NO3, Ca, Mg, and K), which can significantly affect element cycles in mountain forest ecosystems.…”
Section: Overview Of the Special Issue Contributions 21 Hydrological And Atmospheric Aspects Of Natural Hazards In Changing Climate And Ementioning
confidence: 99%
“…The Special Issue we introduce consists of 11 original research papers [1][2][3][4][5][6][7][8][9][10][11] divided into three groups based on research interests, namely, 1. hydrological and atmospheric aspects of natural hazards in changing climate and environment, 2. ecophysiological and ecological water-related impacts of natural hazards, and 3. methodological approaches in natural hazard evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest intensification of heatwaves was evident, particularly in the last decade. Minďaš et al (2020) evaluated the long-term changes in the chemical composition of precipitation in the mountain forests of Slovakia in a forty-one-year period (1987 to 2018). Two stations with long-term measurements of precipitation quality were selected, all basic chemical components were analysed, and changes in the individual components were statistically evaluated.…”
Section: Runoff Fluctuations and Anthropogenic Impacts On Hydrologica...mentioning
confidence: 99%
“…Over the last decades, forest tree species have encountered different drought stress levels. Drought stress is accompanied by a slowdown in assimilation processes and growth, decreased resistance and earlier termination of growing seasons (Minďáš et al 1996;Schneider 1997;Camarero et al 2018;Lukasová et al 2020;Bigler & Vitasse 2021;Mezei et al 2022;Bucha et al 2023), while extreme drought can lead to the death of individual trees or even whole forest stands (Obladen et al 2021;Frei et al 2022). There is a risk that climate change might exceed the ability of European forest trees to adapt to upcoming environmental conditions (Petrik et al 2022), particularly when the rate of global temperature rise is accelerating (Thompson 2010).…”
Section: Introductionmentioning
confidence: 99%